Silicon-, Silica-, and Silicate-Toothpastes for Remineralization and Repair of Teeth: A Scoping Review - Fabio Correia Sampaio; Andressa Feitosa Bezerra de Oliveira; Nayanna Lana Soares Fernandes; Ana Carolina Cheron Gentile; Giovanna Bueno Marinho; Marcelo José Strazzeri Bönecker; Marco Aurelio Benini Paschoal; Paulo Henrique Perlatti D’Alpino; Fabiano Vieira Vilhena (Oral)
Objective: The purpose of this scoping review was to identify gaps in the literature and summarize findings from studies examining the use of silicon-, silica-, and silicate-based toothpastes for the remineralization and repair of mineralized tooth tissues. Methods: A 10-year literature search was conducted using PubMed and Scopus, adhering to PRISMA 2020 guidelines. A total of 331 studies were initially identified, with 56 full-text review articles. After selecting the manuscripts, 27 studies were qualitatively analyzed by four reviewers, focusing on the results of both in vivo and in vitro methods. Results: The findings suggest that toothpastes containing silicon, silica, and silicate demonstrate promising results for remineralization and enamel repair, with evidence of mineral layer formation and/or deep enamel surface remineralization under various conditions. Additionally, the use of these toothpastes can lead to the obliteration of dentinal tubules within a few days. The results collectively support the efficacy of these toothpastes in enamel repair. Most of the clinical studies focused on dentine hypersensitivity, followed by white spot lesions. Conclusions: Silicon-, silica-, and silicate-based toothpastes (bioactive Si-toothpastes) can be considered effective based mostly on laboratory studies. There remains a need for more in vivo research studies on enamel and dentin mineral repair. Existing studies provide strong evidence that these technologies can reduce dentin hypersensitivity and promote enamel–dentin repair.